Modeling and BEM Analysis of Reinforced Concrete Cracked Panels - Minch, Maciej Yan (Communications - Scientific letters of the University of Zilina, 2002)
In this paper the method of distribution solution of RC (reinforced concrete) cracked of the plane stress plates (panels) is shown. The viscoelastic RC cracked plate model has been derived by the variation method of Gurtin in the class of the general function. The total differential equations in the two-dimensional general vector functions are shown. In this model the effect of the discontinuity general deformation vector, bond slip and concrete creep are taken into account. The numerical results of approximate solutions with the method of boundary elements (BEM) are shown.